[Pyridine–SO3H]ZnCl3: A Multipurpose Catalyst for A3 Coupling Synthesis of Propargylamines under Mild Conditions - Moosavi-Zare, Ahmad Reza; Rezaei-Gohar, Mohammad; Tavasoli, Mahsa; Goudarziafshar, Hamid (Synlett, 2023)
N-Sulfopyridin-1-ium monozinc(II) trichloride ([NSPy]ZnCl3) was prepared and used as a multipurpose catalyst for the synthesis of propargylamines by the A3 coupling reaction of aromatic aldehydes, alkynes, and secondary amines under mild conditions. In this reaction, the carbonyl group in the aldehyde was activated by the acidic part in the catalyst, and the C–H activation of phenylacetylene was carried out by zinc.
Keywords: A3 coupling reaction; C–H bond activation; propargylamines; ionic liquid catalysis; amines; multicomponent reaction